Resposta :
Resposta:
Explicação passo-a-passo:
1- 3/4 +1/6 = (9+2)/12 = 11/12
2- 3/5 +1/9 = (27+5)/45 = 32/45
3- 6/5+7/9 = (54+35)/45 = 89/45
Explicação passo-a-passo:
[tex] \frac{3}{4} + \frac{1}{6} = \frac{3 \times 6 + 4 \times 1}{4 \times 6} = \frac{18 + 4}{24} = \frac{22}{24} = \frac{11}{12} [/tex]
[tex] \frac{3}{5} + \frac{1}{9} = \frac{3 \times 9 + 5 \times 1}{5 \times 9} = \frac{27 + 5}{45} = \frac{32}{45} [/tex]
[tex] \frac{6}{5} + \frac{7}{9} = \frac{6 \times 9 + 5 \times 7}{5 \times 9} = \frac{54 + 35}{45} = \frac{89}{45} [/tex]